Multimodal Transport, A Solution for The Implementation of a Sustainable Mobility System in Romania, In Line with The Current EU Policy - Frantz Daniel FISTUNG; Cornelia NEAGU; Marius BULEARCĂ; Cristian SIMA (Communications of International Proceedings, 2022)
The current paper aims to identify the steps taken by Romania in the last decades to support the development of a strong and harmonious multimodal transport system, while highlighting the shortcomings and obstacles encountered in the implementation of this country project. The study aims to present, in the beginning, the general European context, concerning sustainable transportation, generally speaking and multimodality in particular. After that, highlights regarding multimodal activity and specific infrastructure from Romania will offer a perspective for the future development of this activity in Romania. At the end of paper, proposals are also presented to improve the existing situation and accelerate the development of an efficient multimodal transport system in Romania, in line with the national needs and requirements of the Community policy in the field. In this context the paper underline that the EU strategy for sustainable and smart mobility, published in December 2020, underlines that a real solution for reducing energy consumption and imports of petroleum products is undoubtedly the stimulation of the long-term development of multimodal transport. This takes into account that the multimodality of transport leads to the efficient use of modes with capacity reserves (rail, inland waterways and maritime transport) with beneficial effects on energy consumption and pollutant emissions. An important conclusion of this study paper is that the Romanian policy, regarding multimodal transport, must always consider harmonising and integrating actions within European policies in the field and reallocating quotas of different modes by creating the conditions for transferring as much as possible of freight transport from road mode to the most environmentally friendly ones such as the multimodal one.
Keywords: Multimodal transport; Sustainable mobility; Multimodal terminals